Intense continuing currents following positive cloud-to-ground lightning associated with red sprites - Reising, Steven C., author; Bell, Timothy F., author; Inan, Umran S., author; American Geophysical Union, publisher (Colorado State University. Libraries, 1998)
In July-August, 1996, Stanford University carried out broadband ELF/VLF measurements of the magnetic field radiated by positive cloud-to-ground (CC) discharges associated with Red Sprites. We report these measurements for 17 Sprite associated discharges that occurred during a 15 minute period on August 1, 1996. The current and charge moments for each of the events are deduced, and it is found that, in every case, intense continuing currents of ~1 ms duration are responsible for most of the positive charge transfer to ground that precedes the appearance of the Sprite. The time delay between the causative positive discharge and the video field in which the Sprite first appeared varied from 0 to 15 ms for the larger events to as much as 100 ms for the smaller events. We suggest that in the smaller events the removal of significant positive charge during this delay interval is accomplished through a horizontal intracloud discharge.